Seagrass-based platform strategies for sustainable hydroxymethylfurfural (HMF) production: toward bio-based chemical products. (18th August 2021) - Heo, Jae Bok; Lee, Yong-Suk; Chung, Chung-Han
Abstract: Today, sustainable chemistry is a key trend in the chemical manufacturing industry due mainly to concerns over the global environment and resource security. In sustainable chemical manufacture, the choice of a bio-based feedstock plays a pivotal pillar. In terms of feedstock utilization for producing HMF, which is a multivalent platform intermediate easily convertible to valuable chemical products; biopolymers, biofuels, and other important chemicals, seagrass biomasses can be more favorable feedstocks compared with land plant resources due primarily to easy availability and no systematic farming. Moreover, seagrass feedstocks could contribute cost-effectively and sustainably producing HMF by exploiting the beach-cast seagrasses on seagrass-prairies with no feedstock cost, indicating that seagrass biomasses could be a most promising biofeedstock source for sustainable HMF production. We afford a platform bioprocessing technology that has not been attempted before for sustainable HMF production using raw seagrass biomass. This bioprocess can be operated by simple reaction conditions using inorganic Brønsted acids (mainly HCl) and ionic liquid solvents at relatively low temperatures (120–130 °C). In addition, some bioengineering strategies for improving the growth of seagrass biomass and the quantity/quality of nonstructural carbohydrates (starch, sucrose) that can be used as the feeding substrates for HMF production are also discussed. The main aim of this review is to provide some important information about breakthrough bio/technologies conducive to cost-effective and sustainable HMF production.